2012
DOI: 10.1007/s10549-012-2163-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of real-time virtual sonography, a coordinated sonography and MRI system that uses an image fusion technique, on the sonographic evaluation of MRI-detected lesions of the breast in second-look sonography

Abstract: The aim of this study was to verify the utility of second-look sonography using real-time virtual sonography (RVS)-a coordinated sonography with an MRI system that uses an image fusion technique with magnetic navigation-on the sonographic evaluation of MRI-detected lesions of the breast. Of the 196 consecutive patients who were examined with breast MRI in our hospital from 2006 to 2009, those patients who underwent second-look sonography to identify MRI-detected lesions were enrolled in this study. MRI was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…To our knowledge, this is the first report to investigate the detailed imaging of the ALL with US. RVS has previously been used in the identification and biopsy of breast cancers and abdominal tumors [15,16,17,18,19]. These studies suggest that the RVS system can accurately identify these tumors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, this is the first report to investigate the detailed imaging of the ALL with US. RVS has previously been used in the identification and biopsy of breast cancers and abdominal tumors [15,16,17,18,19]. These studies suggest that the RVS system can accurately identify these tumors.…”
Section: Discussionmentioning
confidence: 89%
“…These studies suggest that the RVS system can accurately identify these tumors. Nakano et al reported that of 63 breast lesions, 42 (67%) lesions were identified by conventional US, whereas all lesions were identified by RVS [18]. Kitada et al reported that RVS-guided radiofrequency ablation therapy for hepatocellular carcinomas could be useful for treating hepatocellular carcinomas that are difficult to detect with US [16].…”
Section: Discussionmentioning
confidence: 99%
“…agreement, single rater/measurement (i.e., ICC [2,1]) was performed (15). For intrareader reliability, a two-way mixed-effects model (absolute agreement, single measurement) was computed.…”
Section: Main Pointsmentioning
confidence: 99%
“…The second-look US detection rate of MRI-detected lesions must be influenced by operator dependence. Recently, real-time virtual sonography (RVS) without the influence of operator experience and skill has been shown to significantly increase the second-look US detection rate of breast lesions initially detected at MRI [8][9][10]. The RVS system can coordinate US and MRI images using a magnetic positiontracking system and both US and MRI cutaway images of the same site are simultaneously displayed on one monitor in a side-by-side format in real time ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The RVS system can coordinate US and MRI images using a magnetic positiontracking system and both US and MRI cutaway images of the same site are simultaneously displayed on one monitor in a side-by-side format in real time ( Fig. 1) [8][9][10][11]. If it were possible to increase the successful breast MRI-US correlation with RVS, it would be easier, cheaper and more comfortable for the patient to undergo a USguided biopsy for suspicious lesions identified on breast MRI alone.…”
Section: Introductionmentioning
confidence: 99%